2012
DOI: 10.1071/fp12052
|View full text |Cite
|
Sign up to set email alerts
|

GlyPh: a low-cost platform for phenotyping plant growth and water use

Abstract: Breeding drought-tolerant crop varieties with higher water use efficiency could help maintain food supply to a growing population and save valuable water resources. Fast and accurate phenotyping is currently a bottleneck in the process towards attaining this goal, as available plant phenotyping platforms have an excessive cost for many research institutes or breeding companies. Here we describe a simple and low-cost, automatic platform for high-throughput measurement of plant water use and growth and present i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(71 citation statements)
references
References 34 publications
2
69
0
Order By: Relevance
“…Pereyra-Irujo et al (2012) developed such a low cost platform, which would allow it to be used by academic users and breeders. They tested the platform for measurement of water use efficiency of two different soybean genotypes under different water availability scenarios.…”
Section: Content Of This Special Issuementioning
confidence: 99%
“…Pereyra-Irujo et al (2012) developed such a low cost platform, which would allow it to be used by academic users and breeders. They tested the platform for measurement of water use efficiency of two different soybean genotypes under different water availability scenarios.…”
Section: Content Of This Special Issuementioning
confidence: 99%
“…• Simple and low-cost automatic platform for high throughput measurement of plant water use and growth to assess drought tolerance Pereyra-Irujo et al (2012) Accelerating genetic gains in legumes | 3299 2014; Hoogenboom et al, 2017), modelling interactions of plants, animals, climate, soil, and land management. Teixeira et al (2015), using APSIM, demonstrated the importance of rotations for simulating climate impact assessments and Sennhenn et al (2017) found new niches for short season legumes in Kenya.…”
Section: Crop Growth Simulation and Modelling Approachesmentioning
confidence: 99%
“…In GROWSCREEN [15], leaf area and relative growth rate were measured based on images from a camera placed above an array of seedlings. The phenotyping system GlyPh [19] is a low-cost platform for phenotyping plant growth and water use, which allows the evaluation of plants growing in individual pots. In GlyPh, top-and side-view images of the plants are captured, to measure traits such as height, width, and projected leaf area.…”
Section: Introductionmentioning
confidence: 99%